Severity of Amblyopia and Its Correlation with The Amount of Refractive Error - Ria Sandy Deneska (Majalah Oftalmologi Indonesia, 2015)
Background: To analyze the correlation between the severity of amblyopia and the amount of refractive errorMethods: Patients in outpatient clinic dr Soetomo General Hospital, who was diagnozed as amblyopia, from November 2011 – January 2013, were enrolled in this retrospective study. All subjects were evaluated for subjective refraction using Snellen Chart and objective refraction using streak retinoscopy. The severity of amblyopia determined by the BCVA and the amount of refractive error stated by the spherical equivalent and the amount of cylindrical errors.Result: The subjects of this study was 40 patients (73 eyes) with age 5-11 years old. The range of BCVA was 0,1-0,8 logMAR units, the spherical equivalent of refractive errors were minus 1,5D – 12,75D and the cylindrical errors were minus 0,50 – 5,00D. Statistically, there was correlation between the severity of amblyopia and the spherical equivalent of refractive errors, but there was no correlation with the cylindrical errors.Conclusion: The severity of amblyopia has a correlation with the amount of spherical equivalent of refractive error, but has no correlation with the amount of astigmatism. Key words: Amblyopia, Spherical Equivalent, Cylindrical Error